Effect of Freezing Modes, Storage Time, and Defrosting Methods on Microbiological Quality Parameters of Apricots - Batuch M. Guseynova; Islam H. Asabutaev; Tatyana I. Daudova (Техника и технология пищевых производств)
Introduction. Low-temperature freezing technology extends the shelf life of perishable fruits as it causes a sharp slowdown in the biochemical and microbiological processes in frozen products. However, it cannot provide complete destruction of microorganisms. The present research featured the reaction of apricot microbiota to the technological techniques of shock freezing. The research objective was to study the effect of low-temperature freezing modes (t = –25, –30, and –35°C), storage time (3 and 9 months), methods, and defrosting modes (in air at t = 5 and 22°C; in water at t = 5, 16, and 22°C; under the effect of microwave irradiation) on the surface microflora of apricots. Study objects and methods. The experiment featured apricots of the varieties Uzden, Untsukulskiy Pozdniy, Honobah, Krasnoshchyokiy, and Shalakh. The microbiological profile of defrosted apricots was based on the State Standard. Results and discussion. Fast freezing at t = –25°C provided a better inhibition of epiphytic microflora than at t = –30 and –35°C: aerobic-mesophilic and optionally anaerobic microorganisms – by 65.2–68.6%, yeast – by 61.5–69.0%, and mold – by 59.3–68.4%, compared to their initial content on fresh apricots. During the initial period of refrigeration storage, the number of microorganisms decreased, while the subsequent nine-month storage (t = –18°C) led to a slight increase in microbiota. After nine months of storage, the number of microorganisms on defrosted fruits, depending on the variety, was the following: aerobic-mesophilic and optionally anaerobic microorganisms – 1.2×103–2.0×103 CFU/g, yeast – 14–26 CFU/g, and molds – 75–108 CFU/g. Defrosting of apricots by microwave irradiation resulted in a greater destruction of microorganisms than after traditional thawing in air and water. Conclusion. The results of microbiological studies indicate that the shock freezing technology ensures the production of quick-frozen apricots that meet the requirements of Technical Regulations of the Customs Union No. 021/2011.